Level of Acceptability of Squash Dinner Rolls with Cheese to Selected Home Economics Students in Bestlink College of the Philippines (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
This research supports measuring the level of acceptability of squash dinner rolls with cheese to selected Home Economics students in Bestlink College of the Philippines. The researchers chose this innovative product is because people nowadays do not eat many vegetables. The main source of our data was the data obtained from 60 respondents in Bestlink College of the Philippines. The researchers used experimental research design, survey method, and simple random sampling technique to gather the information of the respondents and know if the product is acceptable. The result showed that 50 students strongly agreed with the taste of squash dinner rolls with cheese, while the 10 other respondents very strongly agreed regarding the taste, aroma, nutritional value, and presentation. These results showed that squash dinner rolls with cheese were acceptable to students and teachers. The researchers focused on determining the level of acceptability of squash dinner rolls with cheese. The researchers showed how to make this product. Based on the information gathered by the researchers, the results showed all respondents strongly agreed to the acceptability of the product in terms of taste and aroma. The ingredients were accurately measured and mixed carefully.
Keywords: dinner rolls with cheese, squash dinner rolls